Design, synthesis, evaluation and molecular modeling studies of some novel N-substituted piperidine-3-carboxylic acid derivatives as potential anticonvulsants - Seth A.; Sharma P.A.; Tripathi A.; Choubey P.K.; Srivastava P.; Tripathi P.N.; Shrivastava S.K. (My University, 2025)
Novel Schiff bases of 1-(2-Aminoethyl)piperidine-3-carboxylic acid were synthesized, characterized and screened for anticonvulsant activity. Compounds were evaluated for in vitro blood–brain barrier (BBB) permeability by parallel artificial membrane permeability BBB assay (PAMPA-BBB). Compounds 5d, 5f, 5j, 5l, 5m, 5n, 5w, 5x and 5y elicited considerable in vitro permeability across BBB and further screened for in vivo anticonvulsant activity by sc-PTZ and DMCM-induced seizure models. The outcome of the in vivo models suggested that 5d, 5w, and 5y were most potent amongst the synthesized compounds. The neurotoxicity evaluation of 5d, 5w, and 5y by rotarod indicates no impairment of muscle coordination in comparison to standard diazepam. The MTT assay revealed that the test compounds (5d, 5w, and 5y) were not found to alter the cell viability considerably. In silico molecular docking and dynamics simulations were carried out on the homology modeled protein of human GABA transporter 1 (GAT1), which exhibited complementary interactions of compound 5w within the active binding pocket. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.